Damage Probability Assessment of Hospital Buildings in Yogyakarta, Indonesia as Essential Facility due to an Earthquake Scenario - Yunalia Muntafi; Nobuoto Nojima; Atika Ulfah Jamal (Journal of the Civil Engineering Forum, 2020)
Indonesia is a country located in an earthquake-prone region, and is characterized by significantly increased peak ground acceleration value. The seismic hazard map of Indonesia stated in SNI 1726-2012 and the current statistics published by PUSGEN in 2017 emphasized on the significance of assessing building damage probabilities, especially for essential structures in Yogyakarta. However, immediate action is required to handle response and recovery operations during and after a disaster. The aim of this study, therefore, is to ascertain the vulnerability and damage probability of hospital buildings in Yogyakarta by employing the 2006 earthquake scenario, where reports showed the destruction of over 156,000 houses and other structures. Furthermore, a Hazard-US (HAZUS) method was used for structural analysis, while a ground motion prediction equation was adopted to produce the building response spectra, following the characteristics of the earthquake incidence. The vital step in this assessment involves building type classification and identification of seismic design levels. However, the damage tendency of buildings is determined using the peak building response, which ensures the generation of capacity curves. The most significant findings on building damage probability value were less than 15% in each damage state (slight, moderate, extensive, complete). In addition, the optimum value was achieved at the minimum level of damage (minor), while the least values were recorded at the highest damage level (complete).